Effects of Dental Crowding on Oral Hygiene Index-Simplified(OHI-S) score in Adult Population of Lahore: An Analytical Study - Hafsa Gul, Um-E-Rubab Shirazi, Momin Bin Fiaz, Asma Rafi Chaudhry, Nida Asad Dar, Arsalan Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To investigate the impact of dental crowding on oral hygiene in adult populations using the Simplified Oral Hygiene Index (OHI-S) as a reference indicator. Methods: The study is designed as an analytical cross-sectional study with a comparison group and was done in multiple dental settings in Lahore, including orthodontic department of a dental college. The sample includes 456 adult patients with or without dental crowding. The oral hygiene of the participants was assessed using the OHI-S, which measures plaque and calculus on six tooth surfaces. The study statistically determined if there is a difference in oral cleanliness between patients with crowding and the control group, and if there is a difference in oral cleanliness between genders among patients with crowding. Results: 55% of the patients were females and 45% of the patients were males. The patients without crowding, there was 11% higher risk observed of getting Moderate OHI-S score as compared to Good OHI-S. Similarly, 13% higher risk was observed to have Poor OHI-S among patients without dental crowding. This risk was markedly increased among patients with dental crowding. Patients with dental crowding were at 57% (P-value <0.05) higher risk of getting Moderate OHI-S score and 89% (P-value <0.05) higher risk of getting Poor OHI-S. Conclusion: Dental crowding is significantly connected to the accumulation of calculus and debris in the crowded areas of dental arches in young people. Crowding has been shown to make it more difficult to maintain appropriate oral hygiene routines. This raises the probability of young adults developing periodontal disease. Keywords: Dental Crowding, Malocclusion, Oral Hygiene.